Exogenous Trehalose Treatment Enhances the Activities of Defense-Related Enzymes and Triggers Resistance against Downy Mildew Disease of Pearl Millet - Govind, Sharathchandra R.; Jogaiah, Sudisha; Abdelrahman, Mostafa; Shetty, Hunthrike S.; Tran, Lam-Son P. (Frontiers in Plant Science, 2016)
In recent years, diverse physiological functions of various sugars are the subject of investigations. Their roles in signal transduction in plant responses to biotic and abiotic stresses have become apparent, and growing scientific evidence has indicated that disaccharides like sucrose and trehalose mediate plant defense responses similar to those induced by elicitors against the pathogens. Trehalose is a well-known metabolic osmoregulator, stress protectant and a non-reducing disaccharide commonly found in a wide variety of organisms, including fungi, bacteria and plants. Commercially procured trehalose was applied to seeds of susceptible pearl millet (Pennisetum glaucum) cultivar “HB3”, and tested for its ability to reduce downy mildew disease incidence by induction of resistance. Seed treatment with trehalose at 200 mM for 9 h recorded 70.25% downy mildew disease protection, followed by those with100 mM and 50 mM trehalose which offered 64.35% and 52.55% defense, respectively, under greenhouse conditions. Furthermore, under field conditions treatment with 200 mM trehalose for 9 h recorded 67.25% downy mildew disease protection, and reduced the disease severity to 32.75% when compared with untreated control which displayed 90% of disease severity. Trehalose did not affect either sporangial formation or zoospore release from sporangia, indicating that the reduction in disease incidence was not due to direct inhibition but rather through induction of resistance responses in the host. Additionally, trehalose was shown to enhance the levels of polyphenol oxidase (PPO), phenylalanine ammonia lyase (PAL) and peroxidase (POX), which are known as markers of both biotic and abiotic stress responses. Our study shows that osmoregulators like trehalose could be used to protect plants against pathogen attacks by seed treatment, thus offering dual benefits of biotic and abiotic stress tolerance.